Felony Murder and Capital Punishment: an Examination of the Deterrence Question - Bailey, William C. (1991)
A proper test of the deterrent effect of the death penalty must consider capital homicides. However, the criterion variable in most investigations has been total homicides—most of which bear no legal or theoretical relationship to capital punishment. To address this fundamental data problem, this investigation used Federal Bureau of Investigation data for 1976–1987 to examine the relationship between capital punishment and felony murder, the most common type of capital homicide. We conducted time series analyses of monthly felony murder rates, the frequency of executions, and the amount and type of television coverage of executions over the period. The analyses revealed occasional departures (for vehicle theft and narcotics killings) from the null hypotheses. However, on balance, and in line with the vast majority of capital punishment studies, this investigation found no consistent evidence that executions and the television coverage they receive are associated significantly with rates for total, index, or different types of felony murder